Ekspresi p16 dan CDK4 pada Berbagai Stadium T Karsinoma Laring - Diana Purnamasari; Dyah Fauziah (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2020)
BackgroundDefect in cell cycle control affect cell proliferation and play an important role in pathogenesis of cancer. Recently, some proteins areknown to have an influence in cell cycle proliferation. P16 and CDK4 may have influenced in laryngeal carcinoma. CDK4, anoncogene, can form cyclin D1-CDK4 complex that inactivates pRb so that the cell cycle goes from G1 phase to S phase. P16, atumor suppressor protein, can prevent cyclin D1-CDK4 complex so that inhibit cell proliferation.MethodsThis research was an observational analysis study with paraffin block samples, consists of 3 samples of stage T1 and each 10samples of stage T2, T3 and T4 in Laboratory of Anatomical Pathology of RSUD dr. Soetomo that was collected from 2013-2015.Samples were stained with antibody of p16 and CDK4. P16 and CDK4 expression were assessed based on the percentage andintensity of tumor cells that were stained. The differences between variables were analyzed by Kruskal-Wallis. The correlationbetween variables was analyzed by Spearman correlation test.ResultsP16 expression of carcinoma larynx T1 (88.33±7.64), T2 (85.00±5.27), T3 (61.00±21.83), and T4 (62.00±25.30). Besides CDK4expression of carcinoma larynx T1 (43.33±15.28), T2 (47.00±14.18), T3 (75.00±8.50), and T4 (70.00±9.43). Statistic analysisshowed significant differences between p16 and CDK4 expression on each stade of carcinoma larynx (p=0.017 and p=0.000). Andthere were corelation between p16 and CDK4 expression on each stage of carcinoma larynx (p=0.000 and p=0.000).ConclusionThe lower p16 expression and the higher CDK4 expression showed the higher stage of carcinoma larynx.